Investigation on fabrication and property of acoustic gradient composites. (18th January 2016) - Dongyu, Xu; Xin, Cheng; Shifeng, Huang
Abstract: Here the acoustic gradient composites were developed by using epoxy resin as matrix and aluminum and iron powders as filling components, respectively, and the density and acoustic properties of the composites in the gradient direction were investigated. When the mass ratio of epoxy resin and aluminum and iron powders is between 1:0.5 and 1:2, the density of aluminum and iron filled composites is 1.4–1.9 gcm −3 and 1.5–4.0 gcm −3, respectively. The density of all the aluminum filled composites presents linear variation in the gradient direction of the composites, however, that of the iron filled composites shows obvious linear variation in the gradient direction of the composites only when the mass ratio of epoxy resin and iron powder is 1:2. The acoustic impedance values of aluminum and iron filled composites are 3–6 Mrayl and 3–9 Mrayl, respectively, and show exponential variations in the gradient direction of the composite.